Analysis of DeFi oracles - Xun Deng; Sidi Mohamed Beillahi; Cyrus Minwalla; Han Du; Andreas Veneris; Fan Long (Bank of Canada, 2024)
This paper presents OVer, a framework designed to automatically analyze the behaviour of decentralized finance (DeFi) protocols when subjected to a "skewed" oracle input. OVer firstly performs a symbolic analysis on the given contract and constructs a model of constraints. Then, the framework leverages a satisfiability modulo theory solver to identify parameters that allow its secure operation. Furthermore, guard statements can be generated for smart contracts that may use the oracle values, thus effectively preventing oracle manipulation attacks. Empirical results show that OVer can successfully analyze all 10 benchmarks collected, which encompass a diverse range of DeFi protocols. Additionally, this paper illustrates that current parameters used in the majority of benchmarks are inadequate to ensure safety when confronted with significant oracle deviations. It shows that existing ad-hoc control mechanisms such as introducing delays are often insufficient or even detrimental to protect the DeFi protocols against the oracle deviation in the real world. Moreover, this paper delves into the design considerations of price oracles within a potential blockchain-based digital currency
Keywords: G; G1; G15; E4; E42; E5; E51; O; O3; O31; 330; Central bank research; digital currencies and fintech; payment clearing and settlement systems